2016
DOI: 10.1177/1533034616655909
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mixed Lineage Kinase Domain-Like Protein Expression With Prognosis in Patients With Colon Cancer

Abstract: Background: The mixed lineage kinase domain-like protein has recently been identified as a key downstream component of tumor necrosis factor-induced necroptosis, which is an important pathway of cancer cell death. The goal of the current study is to explore the expression of mixed lineage kinase domain-like protein in colon cancer tissues and evaluate the prognostic value in patients with colon cancer. Methods: We collected normal and cancer colon tissues from 135 patients diagnosed with colon cancer after rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 19 publications
1
56
1
Order By: Relevance
“…These findings suggest that RIPK3 is a critical tumor suppressor in intestinal inflammation and colitis‐associated colorectal cancer. Similarly, it has been shown that low levels of MLKL (Table ) are associated with decreased overall survival in patients with pancreatic adenocarcinoma, colon cancer and cervical squamous cell carcinoma . MLKL expression is involved in the modulation of local immunosurveillance of the tumor microenvironment (Figure ).…”
Section: The Necroptotic Pathway Is Affected In Many Cancersmentioning
confidence: 87%
“…These findings suggest that RIPK3 is a critical tumor suppressor in intestinal inflammation and colitis‐associated colorectal cancer. Similarly, it has been shown that low levels of MLKL (Table ) are associated with decreased overall survival in patients with pancreatic adenocarcinoma, colon cancer and cervical squamous cell carcinoma . MLKL expression is involved in the modulation of local immunosurveillance of the tumor microenvironment (Figure ).…”
Section: The Necroptotic Pathway Is Affected In Many Cancersmentioning
confidence: 87%
“…As a consequence, a lower expression of necroptosis regulators seems to correlate with a worse prognosis in several types of carcinomas (i.e., breast, colorectal, gastric, and ovarian cancer, and head and neck and cervical squamous cell carcinoma), in acute myeloid leukemia, and in melanoma [30,[42][43][44][45][46][47][48]. However, the expression of RIPK1, RIPK3, and MLKL has been found to be upregulated in some cancers (i.e., glioblastoma, pancreatic, lung, and esophageal cancer), in which a high activation of the necroptotic cascade seems to be correlated with a poorer prognosis in different studies [6,36,41,[49][50][51][52][53]. The role of necroptosis in liver carcinogenesis is also still not clear.…”
Section: Pro-tumoral Effects Anti-tumoral Effectsmentioning
confidence: 99%
“…This indicates that RIPK3 expression may be negatively selected during the development or progression of breast and colorectal cancers. Likewise, reduced expression of MLKL was significantly associated with decreased overall survival of gastric, ovarian, cervix, colon and pancreatic cancers [35][36][37][38][39] (Table 1). Thus, MLKL expression could potentially serve as a prognostic biomarker for those cancers.…”
Section: Prognosismentioning
confidence: 99%